LEGAL PROTECTION AGAINST SALE AND PURCHASE AGREEMENT OF BUILDING USE TITLE IN THE EVENT OF DEFAULT - Murdiana, I Nyoman Gede; Gorda, A.A.A.N Sri Rahayu (Kertha Semaya : Journal Ilmu Hukum; Vol 9 No 1 (2020)DO - 10.24843/KS.2020.v09.i01.p02, 2020)
An agreement will not always be able to run according to the agreement of the parties. Certain conditions can be found, such as, the occurrence of various things that result in an agreement cannot be implemented, namely the buy-back right by the seller which has been agreed upon and results in losses for the buyer and on a court decision that sentences the seller to carry out the agreement seven days after the verdict, but the implementation of the sale and purchase agreement has not yet been carried out. This paper examines the legal protection for the buyer against the sale and purchase agreement for building use rights in terms of default. This type of research is a normative juridical legal research applying a case study approach and statue approach. The preventive legal protection for the buyer, namely legal protection is by requesting for irrevocable power of attorney, referred to as absolute power of attorney. Meanwhile, repressive legal protection is legal protection after the occurrence of a dispute, namely based on the consideration of a judge's decision which can provide a sense of certainty and justice to the aggrieved buyer.   Suatu perjanjian tidak selamanya akan dapat berjalan sesuai dengan kesepakatan para pihak. Kondisi tertentu dapat ditemukan terjadinya berbagai hal yang berakibat suatu perjanjian tidak dilaksanakan yaitu dengan hak membeli kembali oleh penjual yang telah disepakati dan mengakibatkan kerugian bagi pihak pembeli dan atas putusan pengadilan yang menghukum pihak penjual untuk melaksanakan perjanjian tujuh hari setelah putusan, akan tetapi pelaksanaan perjanjian jual beli tersebut belum juga terlaksana. Jenis penelitian ini adalah penelitian hukum yuridis normatif dengan menggunakan pendekatan studi kasus dan pendekatan perundang-undangan. Perlindungan hukum secara preventif bagi pihak pembeli yaitu perlindungan hukum yaitu permintaaan pemberian kuasa yang tidak dapat ditarik kembali yang disebut surat kuasa mutlak. Sedangkan perlindungan hukum secara represif adalah perlindungan hukum setelah terjadinya sengketa yaitu berdasarkan pertimbangan putusan hakim yang bisa memberikan rasa kepastian dan keadilan terhadap pembeli yang dirugikan.